2017
DOI: 10.5194/acp-17-2901-2017
|View full text |Cite
|
Sign up to set email alerts
|

A decadal satellite record of gravity wave activity in the lower stratosphere to study polar stratospheric cloud formation

Abstract: Abstract. Atmospheric gravity waves yield substantial small-scale temperature fluctuations that can trigger the formation of polar stratospheric clouds (PSCs). This paper introduces a new satellite record of gravity wave activity in the polar lower stratosphere to investigate this process. The record is comprised of observations of the Atmospheric Infrared Sounder (AIRS) aboard NASA's Aqua satellite from January 2003 to December 2012. Gravity wave activity is measured in terms of detrended and noise-corrected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(102 citation statements)
references
References 83 publications
7
80
0
Order By: Relevance
“…Similarly, in the Arctic, a slight increase in variance can be seen along the east coast of Greenland. These spatial imprints of gravity wave activity are largely consistent with the patterns identified by the AIRS 15 µm brightness temperature variations (Hoffmann et al, 2017b) and the Antarctic winter monthly-mean E p patterns also derived from COSMIC GPS-RO (Hindley et al, 2015). However, since any kind of wave activity giving rise to vertical temperature fluctuations will increase the calculated variance, non-orographic features are also visible in these COSMIC temperature variance maps.…”
Section: Temperature Fluctuationssupporting
confidence: 84%
See 1 more Smart Citation
“…Similarly, in the Arctic, a slight increase in variance can be seen along the east coast of Greenland. These spatial imprints of gravity wave activity are largely consistent with the patterns identified by the AIRS 15 µm brightness temperature variations (Hoffmann et al, 2017b) and the Antarctic winter monthly-mean E p patterns also derived from COSMIC GPS-RO (Hindley et al, 2015). However, since any kind of wave activity giving rise to vertical temperature fluctuations will increase the calculated variance, non-orographic features are also visible in these COSMIC temperature variance maps.…”
Section: Temperature Fluctuationssupporting
confidence: 84%
“…For example, a study of superpressure balloon measurements by Hoffmann et al (2017a) found that ERA-I, MERRA, and MERRA-2 reproduced about 30 % of the standard deviation of the balloon temperature fluctuations, whereas the lower spatial resolution NCEP/NCAR reanalysis reproduced only 15 % and the higher-resolution ECMWF operational analysis reproduced 60 %. ECMWF analyses also underestimate both gravity wave momentum fluxes derived from the balloon measurements (Jewtoukoff et al, 2015) and wave amplitudes derived from Aqua AIRS (Hoffmann et al, 2017b). Similarly, the COSMIC data should perform better than the reanalyses because of their higher resolution.…”
Section: Temperature Fluctuationsmentioning
confidence: 99%
“…This work is part of a larger effort to compile 25 new reference PSC climatologies based on the contemporary CALIOP, MIPAS, and MLS datasets that is being performed under the auspices of the Stratospheric-tropospheric Processes and their Role in Climate (SPARC) Polar Stratospheric Cloud initiative (PSCi: http://www.sparc-climate.org/activities/polar-stratospheric-clouds/). A separate MIPAS PSC climatology has been compiled by Spang et al (2017). These new climatologies represent the first observational-based records of PSC occurrence, composition, and particle characteristics on vortex-wide spatial scales covering decadal time scales and are a 30 valuable resource for testing and validating current and future global models.…”
Section: Introductionmentioning
confidence: 99%
“…The residual term in equation (4) may be an approximation of the net chemical production term. Some previous studies have suggested that gravity waves could affect polar stratospheric clouds via small-scale temperature fluctuations and that the polar stratospheric clouds induced by gravity waves in the northern hemisphere are nonuniform in the meridional direction (Alexander et al, 2013;Hoffmann et al, 2017;Zhao et al, 2019). The meridional structure of the residual term in Figure 9d is therefore possibly related to the modulation of stratospheric ozone concentrations by gravity waves and molecular diffusion.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 79%